Construction of a mutant library associated with aroma genes in tobacco using CRISPR/Cas9 - ZENG Wanli1, LIANG Gang2, GAO Qian1, LI Yuanchuan3, XU Li1, JIANG Jiarui1, XU Yong1, XIANG Haiying1* (Guangxi Zhiwu)
To explore the feasibility of constructing a tobacco mutant library using the CRISPR/Cas9 gene editing technology, we designed sgRNAs of 100 aroma related genes in tobacco, constructed a plasmid library composed of 100 corresponding CRISPR/Cas9 editing vectors, and analyzed the co-transformation rate, on-target editing rate, and off-target editing of transgenic offspring using the tobacco variety ‘Honghua Dajinyuan' as experimental material in this study. The results were as follows:(1)After co-transformation of 100 sgRNAs mediated by Agrobacterium tumefaciens, 77 of them were detected in 172 positive transformation strains, with a co-transformation rate of 77%.(2)Among 77 transgenic offspring carrying sgRNA, 69 sgRNAs edited the target genes, with an editing rate of 89.6%.(3)Sequencing detection revealed that only one sgRNA produced off-target editing at a non-target site, indicating a very low probability of off-target editing of CRISPR/Cas9 in tobacco. In summary, it is feasible to construct a mutant library by the co-transformation of a CRISPR/Cas9 vector library to edit a large number of candidate target genes in tobacco. This method has the characteristics of high co-transformation rate, high editing rate, and low probability of off-target editing.